2008
DOI: 10.1182/blood-2007-03-079921
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin modifications induced by PML-RARα repress critical targets in leukemogenesis as analyzed by ChIP-Chip

Abstract: IntroductionBalanced translocations that lead to expression of aberrant fusion proteins are a hallmark of acute leukemias. 1 Many of these fusion proteins function as aberrant transcription factors that are an initiating event in leukemogenesis. 2 Some translocations, eg those involving the MLL gene can lead to phenotypically diverse forms of leukemia, whereas the t(15;17) uniformly leads to acute promyelocytic leukemia. The reasons why some translocations are leukemia-type specific, whereas others are not, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 45 publications
1
52
0
1
Order By: Relevance
“…ChIP was carried out as described previously with slight modifications (38). In brief, 3 ϫ 10 7 A673 cells were formaldehyde (1% final) fixed for 10 min.…”
Section: Realmentioning
confidence: 99%
See 1 more Smart Citation
“…ChIP was carried out as described previously with slight modifications (38). In brief, 3 ϫ 10 7 A673 cells were formaldehyde (1% final) fixed for 10 min.…”
Section: Realmentioning
confidence: 99%
“…ChIP was carried out with 3 g of antibody either anti-FLI1 (C-19), or anti-IgG (Santa Cruz) added to 0.5 mg of precleared chromatin. Quantitative real-time PCR by using Sybr Green (Applied Biosystems) with quantitation performed by the ⌬⌬Ct-method (38). FLI1 data at individual genomic loci were normalized to the IgG control to compensate for differences in PCR efficiency, and standardized to 2 nonregulated genomic loci outside of the EZH2 locus.…”
Section: Realmentioning
confidence: 99%
“…Accordingly, PML-RARa has been shown to induce APL in transgenic mice. 3 However, deregulation of the retinoic acid pathway is insufficient to initiate APL, 4 and several studies have shown additional genetic and epigenetic processes that accompany the expression of the PML-RARa protein, 5,6 also involving master transcription regulators 7 and modulators of chromatin structure. 8,9 MicroRNAs (miRNAs) are single-stranded small noncoding RNAs (sncRNAs) that negatively regulate the expression of target genes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to increased repressor activity, the PML/RARA fusion also appears to possess a considerable expanded repertoire of target genes compared to the n o r m a l R A R A p r o t e i n . T h i s n o t i o n i s supported by in vitro binding studies showing that PML/RARA has a broader and more relaxed DNA binding specificity compared to RARA (Hauksdottir & Privalsky, 2001;Kamashev et al, 2004), and by a genome wide screen revealing a wide range of PML/RARA target genes (Hoemme et al, 2008). The altered DNA binding and transcription repression properties of PML/RARA are partially due to the ability of this chimeric protein to form homodimeres through protein-protein interactions mediated by the TRIM motif of PML (Jansen et al, 1995;Perez et al, 1993).…”
Section: The Function Of Pml/raramentioning
confidence: 95%